2023
DOI: 10.3390/nano13071238
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Thermophysical Properties of GNP-Fe2O3 Hybrid Nanofluid: Effect of Volume Fraction and Temperature

Abstract: The study focused on the impact of concentration and temperature on the electrical conductivity, viscosity, and thermal conductivity of GNP/Fe2O3 hybrid nanofluids. The study found that nanofluids have better electrical conductivity, viscosity, and thermal conductivity than water. The electrical conductivity and thermal conductivity increase linearly with concentration for a constant temperature. However, the nanofluid’s viscosity increases with the addition of the hybrid nanoparticles and decreases as the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The visualization technique [ 30 , 31 ] and zeta potential analysis (ZetaPALS-1) are effective methods for analyzing the stability of magnetic nanofluids. Figure 3 a shows the samples of the magnetic nanofluid with volume fractions of 0.2%, 0.5%, and 1%.…”
Section: Methodsmentioning
confidence: 99%
“…The visualization technique [ 30 , 31 ] and zeta potential analysis (ZetaPALS-1) are effective methods for analyzing the stability of magnetic nanofluids. Figure 3 a shows the samples of the magnetic nanofluid with volume fractions of 0.2%, 0.5%, and 1%.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the unique properties of the nanofluid, the thermal conductivity of the fluid can either rise or decrease with increasing concentration. According to research by Borode et al, [35] and Darabian et al, [36], as concentration increases, a nanofluid's thermal conductivity decreases. On the other hand, additional research has demonstrated that as concentration increases, the nanofluids' thermal conductivity also can increase [37,38].…”
Section: Thermophysical Properties Of Nanofluids 331 Thermal Conducti...mentioning
confidence: 98%
“…Harandi et al [16] reported a 30% increase in the conductivity coefficient at a temperature of 50 • C and a volumetric fraction of 2.3% of hybrid nanofluids composed of Fe 2 O 3 nanoparticles, multi-walled carbon nanotubes, and ethylene glycol as the base fluids. Most of the research works carried out with hybrid nanoparticles, i.e., graphene/Fe 2 O 3 -added water-based nanofluids, have shown such enhancements in thermo-physical properties [17]. Furthermore, a recent experiment verified that Fe 2 O 3 /water-based nanofluids enhanced thermal conductivity by 21.35% at 0.08% volume fraction of Fe 2 O 3 [18].…”
Section: Introductionmentioning
confidence: 98%